Emerging technologies towards extracellular vesicles large-scale production - Junjie Huang; Hanxu Chen; Ning Li; Panmiao Liu; Jianjun Yang; Yuanjin Zhao (Bioactive Materials)
Extracellular vesicles (EVs), which carry bioactive components such as proteins and nucleic acids, reflect the physiological state of their parent cells and play a key role in mediating complex intercellular signaling. Leveraging these unique characteristics, researchers have explored their potential applications in cell therapy, non-invasive biopsies, and tissue regeneration. Therefore, standardized and scalable methods for EVs production and purification are crucial for clinical application and therapeutic settings. However, the limited yields of traditional production and isolation methods have hampered full potential of EVs. In this review, we will introduce strategies aimed at enhancing EV production include optimizing cell yield, expanding cell culture scale, and exploring alternative EVs production sources such as non-mammalian organisms and artificially produced vesicles. Various approaches as well as the bioreactors for controlling cell culture to enhance EVs production, will be introduced in detail. These approaches include regulation of culture parameters, culture medium components, and external stimuli. Additionally, the comparison between traditional ultracentrifugation methods and advance microfluidic isolating methods will be analyzed and discussed. Finally, we will introduce the potential challenges of transitioning EVs from basic research to clinical application and further discuss the future prospects. As the technology advances and different methods are integrated, there is significant potential to enable large-scale EVs production and improve their clinical translation.